Preservation of Terrestrial Microorganisms and Organics Within Alteration Products of Chondritic Meteorites from the Nullarbor Plain, Australia - Tait, A.W.; Wilson, S.A.; Tomkins, A.G.; Hamilton, J.L.; Gagen, E.J.; Holman, Alex; Grice, Kliti; Preston, L.J.; Paterson, D.J.; Southam, G. (MARY ANN LIEBERT, INC, 2022)
Meteorites that fall to Earth quickly become contaminated with terrestrial microorganisms. These meteorites are out of chemical equilibrium in the environments where they fall, and equilibration promotes formation of low-Temperature alteration minerals that can entomb contaminant microorganisms and thus preserve them as microfossils. Given the well-understood chemistry of meteorites and their recent discovery on Mars by rovers, a similarly weathered meteorite on Mars could preserve organic and fossil evidence of a putative past biosphere at the martian surface. Here, we used several techniques to assess the potential of alteration minerals to preserve microfossils and biogenic organics in terrestrially weathered ordinary chondrites from the Nullarbor Plain, Australia. We used acid etching of ordinary chondrites to reveal entombed fungal hyphae, modern biofilms, and diatoms within alteration minerals. We employed synchrotron X-ray fluorescence microscopy of alteration mineral veins to map the distribution of redox-sensitive elements of relevance to chemolithotrophic organisms, such as Mn-cycling bacteria. We assessed the biogenicity of fungal hyphae within alteration veins using a combination of Fourier-Transform infrared spectroscopy and pyrolysis gas chromatography-mass spectrometry, which showed that alteration minerals sequester and preserve organic molecules at various levels of decomposition. Our combined analyses results show that fossil microorganisms and the organic molecules they produce are preserved within calcite-gypsum admixtures in meteorites. Furthermore, the distributions of redox-sensitive elements (e.g., Mn) within alteration minerals are localized, which qualitatively suggests that climatically or microbially facilitated element mobilization occurred during the meteorite's residency on Earth. If returned as part of a sample suite from the martian surface, ordinary chondrites could preserve similar, recognizable evidence of putative past life and/or environmental change.